2011
DOI: 10.1002/jcc.21818
|View full text |Cite
|
Sign up to set email alerts
|

Conformational state‐specific free energy differences by one‐step perturbation: Protein secondary structure preferences of the GROMOS 43A1 and 53A6 force fields

Abstract: The one-step free energy perturbation approach can be applied to obtain conformational state-specific free energy differences (FEDs) associated with changes in force field parameters, and thus offers the possibility to consider conformational equilibria during force field parameterization. In this work, using the alanine decapeptide in explicit water solution as a model, the α-helical and β-hairpin state-specific FEDs associated with force field changes between two widely used parameter sets of the GROMOS forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 42 publications
2
18
0
1
Order By: Relevance
“…They also demonstrated that AMBER99SB*‐ILDN results in a better helix‐coil balance than AMBER99SB‐ILDN for the same peptide system . Lin et al pointed out differences in the two GROMOS96 parametrizations concerning the stabilization of α‐helical states. In fact, they showed that α‐helical states in the 43A1 parameter is approximately 15 kJ/mol more stable than in the 53A6 parameter set .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also demonstrated that AMBER99SB*‐ILDN results in a better helix‐coil balance than AMBER99SB‐ILDN for the same peptide system . Lin et al pointed out differences in the two GROMOS96 parametrizations concerning the stabilization of α‐helical states. In fact, they showed that α‐helical states in the 43A1 parameter is approximately 15 kJ/mol more stable than in the 53A6 parameter set .…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al pointed out differences in the two GROMOS96 parametrizations concerning the stabilization of α‐helical states. In fact, they showed that α‐helical states in the 43A1 parameter is approximately 15 kJ/mol more stable than in the 53A6 parameter set . Our results for these two parametrization sets correspond to these observations.…”
Section: Discussionmentioning
confidence: 99%
“…These parameter sets are often selected in performance studies where force fields are assessed and compared [ 22 25 ], and where it is shown that it is still one of the best united-atom force fields available, providing in some cases even better results than some all-atom force fields. Additionally, it is known since a while that the 43A1 parameter set provides better alpha/beta relative stabilities than GROMOS parameter sets developed later [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The simulations were carried out with Gromacs 4.5 with the modified GROMOS96 43a1p force field containing the parameters for phosphoserine. This force field was shown to give a balanced description of secondary structural elements without any bias or preference . A time step of 2 fs was used.…”
Section: Methodsmentioning
confidence: 99%